2011
DOI: 10.1126/scitranslmed.3002346
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Reverses Cellular Phenotypes and Enhances Mutant Protein Clearance in Hutchinson-Gilford Progeria Syndrome Cells

Abstract: Hutchinson-Gilford progeria syndrome (HGPS) is a lethal genetic disorder characterized by premature aging. HGPS is most commonly caused by a de novo single-nucleotide substitution in the lamin A/C gene (LMNA) that partially activates a cryptic splice donor site in exon 11, producing an abnormal lamin A protein termed progerin. Accumulation of progerin in dividing cells adversely affects the integrity of the nuclear scaffold and leads to nuclear blebbing in cultured cells. Progerin is also produced in normal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
311
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 309 publications
(340 citation statements)
references
References 37 publications
(54 reference statements)
26
311
1
2
Order By: Relevance
“…In fact, Snell/Dwarf mice-derived fibroblasts show lower levels of mTORC1 activity and enhanced autophagy in response to stress (Wang and Miller 2012). Similarly, we and others show that prolonged reduction of mTORC1 signaling increases autophagy and delays cellular senescence (Demidenko et al 2009;Lerner et al 2013;Cao et al 2011). Since the expression of p62/SQSTM1 is critical to prevent so many age-related processes and is necessary for the beneficial effects of rapamycin on human cells, it is possible that the pro-longevity effects of reducing IGF-1/mTORC1 signaling are due, at least in part, to altered p62/SQSTM1 dynamics.…”
Section: P62/sqstm1: a Novel Aging Genesupporting
confidence: 67%
“…In fact, Snell/Dwarf mice-derived fibroblasts show lower levels of mTORC1 activity and enhanced autophagy in response to stress (Wang and Miller 2012). Similarly, we and others show that prolonged reduction of mTORC1 signaling increases autophagy and delays cellular senescence (Demidenko et al 2009;Lerner et al 2013;Cao et al 2011). Since the expression of p62/SQSTM1 is critical to prevent so many age-related processes and is necessary for the beneficial effects of rapamycin on human cells, it is possible that the pro-longevity effects of reducing IGF-1/mTORC1 signaling are due, at least in part, to altered p62/SQSTM1 dynamics.…”
Section: P62/sqstm1: a Novel Aging Genesupporting
confidence: 67%
“…17,20,21 We recently found that the mTOR inhibitor rapamycin rescues the cellular phenotype of HGPS fibroblasts and decreases the amount of progerin protein through autophagic clearance. 22 Co-treatment with rapamycin and the autophagy inhibitors bafilomycin A1 or 3-methyladenine slow the enhanced clearance, suggesting that progerin is being cleared through autophagy. Further experiments using genetic inhibition of autophagy by ATG7 knockdown confirmed this result.…”
Section: Rapamycin Promotes Clearance Of Progerinmentioning
confidence: 99%
“…3,4,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] This prominent morphological abnormality appears to be caused by expression of farnesylated progerin at the nuclear envelope, as blocking protein prenylation significantly restores normal nuclear shape. [16][17][18][19][20][21][25][26][27]30 The normalization of nuclear shape induced by blocking progerin prenylation correlates with an amelioration of disease phenotypes in mouse models of HGPS.…”
Section: Blocking Farnesylation Of the Prelamin A Variant In Hutchinsmentioning
confidence: 99%